Nanostructuring Lipophilic Dyes in Water Using Stable Vesicles, Quatsomes, as Scaffolds and Their Use as Probes for Bioimaging. Issue 16 (24th March 2018) - Ardizzone, Antonio; Kurhuzenkau, Siarhei; Illa‐Tuset, Sílvia; Faraudo, Jordi; Bondar, Mykhailo; Hagan, David; Van Stryland, Eric W.; Painelli, Anna; Sissa, Cristina; Feiner, Natalia; Albertazzi, Lorenzo; Veciana, Jaume; et al.
Abstract: A new kind of fluorescent organic nanoparticles (FONs) is obtained using quatsomes (QSs), a family of nanovesicles proposed as scaffolds for the nanostructuration of commercial lipophilic carbocyanines (1, 1′‐dioctadecyl‐3, 3, 3′, 3′‐tetramethyl‐indocarbocyanine perchlorate (DiI), 1, 1′‐dioctadecyl‐3, 3, 3′, 3′‐tetramethyl‐indodicarbocyanine perchlorate (DiD), and 1, 1′‐dioctadecyl‐3, 3, 3′, 3′‐tetramethyl‐indotricarbocyanine iodide (DiR)) in aqueous media. The obtained FONs, prepared by a CO2 ‐based technology, show excellent colloidal‐ and photostability, outperforming other nanoformulations of the dyes, and improve the optical properties of the fluorophores in water. Molecular dynamics simulations provide an atomistic picture of the disposition of the dyes within the membrane. The potential of QSs for biological imaging is demonstrated by performing superresolution microscopy of the DiI‐loaded vesicles in vitro and in cells. Therefore, fluorescent QSs constitute an appealing nanomaterial for bioimaging applications. Abstract : Nanostructuring lipophilic dyes in water using stable vesicles, quatsomes, leads to a new class of fluorescent nanoparticles with superior stability and structural homogeneity. The new probes show enhanced optical properties (i.e., brightness) when compared to other nanoparticles and are suitable for application in superresolution microscopy techniques (stochastic optical reconstruction microscopy). Fluorescent quatsomes constitute a promising nanomaterial for imaging and theranostics applications.